2023
DOI: 10.3389/fmicb.2023.1144026
|View full text |Cite
|
Sign up to set email alerts
|

Decay of enveloped SARS-CoV-2 and non-enveloped PMMoV RNA in raw sewage from university dormitories

Abstract: IntroductionAlthough severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) RNA has been frequently detected in sewage from many university dormitories to inform public health decisions during the COVID-19 pandemic, a clear understanding of SARS-CoV-2 RNA persistence in site-specific raw sewage is still lacking. To investigate the SARS-CoV-2 RNA persistence, a field trial was conducted in the University of Tennessee dormitories raw sewage, similar to municipal wastewater.MethodsThe decay of enveloped SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This immediate processing could affect virus concentrations due to variations in decay rates and variability between the enveloped SARS-CoV-2 and non-enveloped PMMoV. Research conducted by Li et al (2023) has indicated a faster decay rate of SARS-CoV-2 RNA compared to PMMoV RNA in raw sewage. PMMoV RNA exhibited higher abundance and lower variability than pathogenic SARS-CoV-2 RNA (Li et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This immediate processing could affect virus concentrations due to variations in decay rates and variability between the enveloped SARS-CoV-2 and non-enveloped PMMoV. Research conducted by Li et al (2023) has indicated a faster decay rate of SARS-CoV-2 RNA compared to PMMoV RNA in raw sewage. PMMoV RNA exhibited higher abundance and lower variability than pathogenic SARS-CoV-2 RNA (Li et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Li et al (2023) has indicated a faster decay rate of SARS-CoV-2 RNA compared to PMMoV RNA in raw sewage. PMMoV RNA exhibited higher abundance and lower variability than pathogenic SARS-CoV-2 RNA (Li et al 2023). A study by Ye et al (2016) found that up to 26% of enveloped viruses (murine hepatitis virus and Pseudomonas phage φ6) adsorbed to the solid fraction of wastewater, compared to 6% of non-enveloped viruses (Enterobacteria phage MS2 and T3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extraction was performed using the Qiagen viral RNA Mini Kit, following the instructions of the manufacturer, yielding 60 μL of extracted RNA, with a negative control using DNase/RNase-free water. Subsequently, the RNA samples were stored at -80°C and subjected to RT-qPCR analysis within 24 h following extraction (Ash et al 2023, Li et al 2023).…”
Section: Methodsmentioning
confidence: 99%
“…To comprehensively understand such sewage, measurements of indicators associated with human waste or fluids are conducted simultaneously with the assessment of SARS-CoV-2 RNA load. Pepper Mild Mottle Virus (PMMoV) is systematically assessed with wastewater due to its acknowledged stability and minimal RNA load variation over time ( Li et al, 2023a , b ). This virus has been employed to detect pathogenic enteric viruses, as heightened RNA load of PMMoV often indicate increased levels of fecal contamination ( Kitajima et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%